Sex differences in longitudinal pathways from parenting to delinquency - Janssen, Heleen (European journal on criminal policy and research, 2017)
In the current study, we examined longitudinally whether boys and girls differed in pathways from parenting to delinquency. Longitudinal mediational models were tested for boys and girls separately in which three parenting dimensions (i.e., monitoring, limit setting, and the quality of the parent-adolescent relationship) were hypothesized to influence adolescents’ level of self-control, delinquent attitudes, peer delinquency, and time spent in criminogenic settings, which in turn, were hypothesized to affect delinquency. Using data of 603 adolescents (11–17 years of age at T1) we found mean level differences between boys and girls in parental monitoring, parental limit-setting, self-control, delinquent attitudes, and peer delinquency. The results suggest furthermore that the model linking parenting to delinquency is similar for boys and girls. We found, however, that the indirect effect from the quality of the parent-adolescent relationship through self-control is stronger for girls than for boys.